Effect of (he using artificial sweeteners instead of sucrose level on the some quality characteristics of ice cream - Ahmet Güner (Eurasian Journal of Veterinary Sciences)
This investigation was done to determine the effect of the using artificial sweeteners instead of sucrose level on the some quality charactersitics of ice cream. For this purpose, aspartame and aspaname-acesulfame K were used certain quantity it is equivalent to sucrose's sweeteen. Reducing of sucrose caused decreasing in ice cream mix density, overrun and total dry solids of ice cream and affected the sensory properties negatively. It was determined that aspartame had more positive effect on the taste compared to ice creams having aspartame-acesulfame K. In conclusion, it was convicted that to compensate quality defects occuned at reducing ol sucrose content of ice cream, fat and non fat milk solids amount of ice cream should be increased, and also in the production ol low sucrose or sucrose free ice cream, aspartame could be preferred.